University students' use of motivational regulation during one semester. (August 2021) - Garn, Alex C.; Morin, Alexandre J.S.
Abstract: This study examined the interplay between university students' trajectories of motivational regulation and autonomous motivation across one semester, exploring both between and within person components. Participants (N = 193) from one large class reported motivation in two-week intervals over the course of one semester. Bivariate latent curve models with structured residuals revealed rates of change in motivational regulation and autonomous motivation were not linear, declining across the first ten weeks of the semester then bouncing back in the final month. Between-person effects of individual change demonstrated mirroring relationships of latent intercepts and slopes across the semester. Within-person findings revealed that autonomous motivation was a negative predictor of future motivation regulation. Students' grade point average only predicted students' beginning level of motivational regulation. It appears that students with higher states of autonomous motivation view motivation regulation as unnecessary or even a potential threat to their learning pleasure and satisfaction. Highlights: Autonomous motivation and motivation regulation showed nonlinear rates of change. Trait-like aspects of motivation mirrored one another over time. State-like autonomous motivation reduced future motivation regulation. Educational interventions must consider both trait and state motivation.